Risk factors for chronic kidney disease: a hospital based cross sectional study from Visakhapatnam - Moparthi, Sindhura; Seepana, Madhavi; Bhimarasetty, Devi Madhavi (International Journal Of Community Medicine And Public Health, 2018)
Background: Chronic kidney disease (CKD) is being increasingly recognised as a leading public health problem. In India, given its population >1 billion, the rising incidence of CKD is likely to pose major problems for both healthcare and the economy in future years. Diabetes and hypertension are strong predictors for development and progression of chronic kidney disease. The objective of the study was to assess risk factors for chronic kidney disease among patients undergoing dialysis in King George Hospital (KGH), Visakhapatnam. Methods: This is an observational descriptive cross sectional study done in dialysis unit in KGH. A total of 100 patients were selected out of 141 registered CKD patients by simple random sampling technique. Study is done in the month of October- November 2015. A pretested semi structured schedule was administered. Informed written consent was taken from the patients. MS excel 2007 was used for data entry. Data was analysed by SPSS trial version 20. Categorical data was analysed by Chi square test. Results: Among 100 study subjects 72 were females and 28 were males. 91% of the CKD patients were Hypertensive, among whom 73.6% were males and 26.4% were females. This difference was not found to be statistically significant (p=0.446). 22% of the CKD patients were Diabetic, among whom 81.8% were males and 18.2% were females. Conclusions: Better understanding of the role of risk factors in CKD is needed. Large community based cross sectional studies are needed to study in detail about CKD risk factors.